Agensi Perempuan dalam Krisis Air di Komunitas Pesisir Urban: Sebuah Kajian Ekofeminisme dan Spiritualitas Islam - Annisa, Tri Indah; Azizah, Nur (Pustaka Peradaban, 2025)
This article explores the intersection of clean water crises and the burden of gendered labor in the informal community of Muara Baru, North Jakarta, through the lens of ecofeminism and Islamic spirituality. In this coastal urban slum, women not only bear the brunt of ecological and infrastructural failures but also emerge as key agents in grassroots environmental resistance. The study reveals how structural inequalities—urban policies blind to gender, water privatization, and discriminatory land tenure requirements—disproportionately impact women, intensifying their domestic and ecological responsibilities. Drawing on the principles of ecofeminism, this paper highlights women's adaptive strategies, localized ecological knowledge, and collective actions in advocating for equitable water access. Their agency is further interpreted as an embodiment of Islamic ethical values such as rahmah (compassion), tawāzun (balance), and mas’ūliyyah (responsibility), reflecting a deeply rooted spiritual consciousness in environmental stewardship. These values align with the Qur’anic vision of humans as khalifah (vicegerents) entrusted to protect and sustain the Earth. Theoretically, this study expands critical ecofeminist discourse by integrating Islamic spirituality as a transformative ethical framework for environmental justice. Practically, it offers insights into the need for inclusive water governance, gender-responsive urban planning, and the amplification of women’s roles in ecological decision-making. In times of accelerating ecological degradation, the experiences of women in Muara Baru point to an urgent call for spiritual-ethical realignment in environmental policy and community resilience. Artikel ini mengkaji keterkaitan antara krisis air bersih, ketimpangan gender, dan spiritualitas dalam perspektif ekofeminisme Islam, dengan studi kasus di Muara Baru, Jakarta Utara. Wilayah pesisir ini menghadapi tantangan ekologis akut, mulai dari penurunan muka tanah, ekstraksi air tanah berlebih, hingga akses air bersih yang diskriminatif bagi komunitas informal. Penelitian ini bertujuan untuk mengeksplorasi bagaimana perempuan—yang menanggung beban ganda dalam rumah tangga sekaligus dalam perjuangan memperoleh hak atas air—berperan sebagai agen perubahan dalam krisis ini. Dengan menggunakan pendekatan kualitatif berbasis studi pustaka, analisis dokumentasi lapangan, dan tinjauan literatur ekofeminisme serta spiritualitas Islam, artikel ini mengungkap bahwa agensi perempuan di Muara Baru tidak hanya bersifat praktis, tetapi juga merefleksikan nilai-nilai religius seperti rahmah (kasih sayang), tawāzun (keseimbangan), dan mas’ūliyyah (tanggung jawab). Temuan ini menunjukkan bahwa spiritualitas Islam dapat menjadi kerangka etis dalam memahami relasi manusia-alam secara lebih adil dan lestari. Artikel ini juga merekomendasikan model pengelolaan air yang partisipatif dan berkeadilan, dengan mengintegrasikan nilai-nilai ekofeminisme dan etika Islam sebagai kontribusi terhadap paradigma pembangunan berkelanjutan yang lebih inklusif